The postulate of rationality in teaching philosophy - Woźniczka, Maciej (Folia Philosophica, 2003)
The author shows that the postulate of rationality in teaching philosophy seems to be so obvious that it is hardly possible to voice any reservations against it. But this is true only of the varieties of philosophy that are closely related to science. Some problems may appear in the case of a broader understanding of philosophy, that is the one that oversteps the limits of pure science. What is emphasised in such a convention, and is particularly important in the philosophical education, is rather the role of experience, intuition or even feelings and emotions. They are assigned a different meaning in educational theory and a different one in educational pragmatics. In keeping with this broader interpretation of the process of the teaching of philosophy, the role of the description of rationality against the background of educational factors becomes more important. It is the precisely the latter that are the subject of the author’s present analysis.